Discharge of CO2 from large‐diameter orifices: Experimental data and data review. Issue 4 (7th October 2015) - Witlox, Henk W. M.; Brown, Jock; Holt, Hamish; Armstong, Keith; Allason, Daniel
Abstract : The CO2PIPETRANS Joint Industry Project included a large‐diameter CO2 release experimental program involving eight dense phase CO2 experiments at the DNV GL Spadeadam test site. The releases were through 1″, 2″, 4″, and 6″ orifice diameters. Measurements included pressure and temperature at several locations in the supply reservoir, feed lines, and discharge pipe, while direct flow rate measurements were carried out for the 1″ releases only. Flow rates for the larger releases were estimated by calculation. This article describes the experiments and presents the results of a high‐level data review of these experiments. As part of the data review, a method was derived to estimate the time‐varying flow rate analytically from derived pressure and temperature measurements in the reservoir. Pressure, temperature, and derived flow rate measurements were analyzed for the subsequent stages of flow in the experiments. The data review concluded that while the data will be very valuable for model validation, the quality of the data measurements for the large‐scale diameter experiments is not as high as the previous smaller‐scale diameter BP and Shell tests due to difficulties making such accurate measurements at the large scale required. © 2015 American Institute of Chemical Engineers Process Saf Prog 34: 389–397, 2015